Marketing management vs. internal management problems (Customer service) in 4life Research Sdn Bhd / Nor Asman Che Mansor - Che Mansor, Nor Asman (Faculty of Business and Management, 2009)
Marketing management is a business discipline which is focused on the practical application of marketing techniques and the management of a firm's marketing resources and activities. In the organization, the company and the employee have a mutual need where the company insists on the revenue through the employee performance. The more quality the employee performs the higher revenue the company achieve especially private sector. From the very beginning, 4Life has been redefining boundaries. They pursuits in Transferceutical Science have led to one surprising discovery, innovation, and patent after another. And their early success positioned them to introduce 4Life Transfer Factor and the Life Rewards Plan to the globe. In the corporate sector, it may change the perception of others towards the operation of the organization. It consists of many problems that the organization could not detect for a certain reason including the internal and the external problem. Many companies claim that they are the best among the others but what can be said is that the company can only claim for the external purpose but internally automatically it different. 4Life have a good way of increasing their good performance of the customer service operation but what the issue behind the good thing is that it is to over the nature of the job description of the customer service. The issue come arrive is that welfare such company provide are fully utilized the employee welfare such stated in the company policy. It is over reacted of the policy. The welfare given by the company is not enough. In conclusion and recommendation, the company and other organization trying their best to achieve that title to present their company to the world as a best management to the eyes of the world. To achieve the target, there are many circumstances that should company appropriately follow standardize with many problems around them.